Macular function testing in a German pedigree with North Carolina macular dystrophy - Rohrschneider, Klaus; Blankenagel, Anita; Kruse, Friedrich E.; Fendrich, Thomas; Völcker, Hans Eberhard (Retina, 1998)
Background: Our purpose was to investigate central visual function in North Carolina macular dystrophy (MCDR1). A German family with genetically proven MCDR1 was followed for more than 20 years. Methods: In addition to routine clinical examinations, static and kinetic fundus perimetry was performed with the scanning laser ophthalmoscope. The center of fixation was determined.Results: Visual acuity was 0.6 or better in all but one eye of seven members of this family and did not markedly change during follow-up. Fundus examination confirmed that the fixation was at the nasal edge of the central scar in five affected eyes with reduced stability of fixation. One eye had a prominent gliotic membrane, and fixation was within this area. Conclusions: Patients had nearly normal visual acuity even though they presented with deep central scotomas and a shift of the center of fixation away from the fovea. Because MCDR1 has good long-term functional prognosis, there might be an early transdifferentiation of the new locus of fixation.